Game-Based Learning and Academic Performance Among Pupils - Wenie L. Nahial; Bernice Anne T. Deiparine (Future Science / FSH-PH Publications, 2026)
Existing learning gaps in schools have drawn considerable attention from teachers in public schools in the Philippines. Due to this, teachers employed various teaching approaches to address the pupils' dismal performance. It is therefore the intention of this work to investigate the utilization of a game-based approach in teaching English and its relationship to the academic performance of learners. Following the observance of research protocols, 45 Key Stage 2 teachers voluntarily participated as respondents in the study. A quantitative descriptive research design was employed in this inquiry. A survey questionnaire supplemented with a casual interview was used to gather the required data from the respondents. Appropriate statistical tools were used to produce reliable results. The analysis revealed that the majority of respondents were young adults in the mid-career stage of their teaching profession and had already earned units in a master’s degree program. Large school sizes and at least six (6) trainings attended have the highest counts in their respective groups. The respondents similarly perceived all the indicators to a high extent, producing an overall impression that they always utilized a game-based approach in teaching English among their pupils. At the time the respondents claimed to have always used a game-based approach, the pupils achieved a “Very Satisfactory” performance level. However, the extent of utilization of the game-based approach did not affect or contribute to the academic performance of the pupils. There may be a tendency for academic performance to decline as the utilization of the game-based approach decreases.